The comparative analysis of the EU and Lithuanian legal transport regulations - Spruogis, Ernestas (Transport, 2005)
The significance of the transport economy determines such a fact that the State and its institutions have a duty to look over this economic branch very narrowly. This duty is especially important while guaranteeing conditions for the fair competition in the transport sector. The author presents the analysis of the EU and Lithuanian legal transport competition regulations. The conclusion is drawn that the national legal competition regulation complies with the EU legal competition regulation; the EU legal transport competition regulation is much more detailed than national legal transport competition regulation in Lithuania. First Published Online: 27 Oct 2010